Pendidikan Pranatal Perspektif Islam dari Kisah Maryam - Muhammad Shodiq Masrur (Journal of Islamic Education Research, 2021)
This article examines the prenatal education of children according to the letter Maryam with the aim of seeing and describing the process of prenatal education that Maryam did to educate the prophet Isa before birth. This research include literature research using descriptive qualitative methods. Data collection in this case prefers to identify discourse from the Alquran, books, journals or other information related to the research title. The data analysis technique used is content analysis of the collected data. The results of this study indicate that the first of the psychological aspects shown by Maryam in the process of prenatal education is always being obedient in worship, dzhikr and having enough rest to stay away from things that can cause stress, in this way it will directly impact the child to worship Allah. Second, the physical aspects shown by Maryam in the prenatal education process can include the stages of choosing a mate who has a religious attitude, the stages of biological relationships and the stages of consumsing nutritious foods (dates). In this way it will have a good impact on the growth and development of fetal life, to the level of intelligence of children after birth.